La licence obligatoire : outil emblématique de la protection de la santé publique au Sud - Samira Guennif (Revue de la Régulation)
Is compulsory licensing good for public health in the South? This paper proposes a survey of the literature examining the link between this flexibility provided by the TRIPS Agreement, which authorizes the suspension of a monopoly related to a patent and the local production of generics, and drug accessibility in developing countries. On the basis of a conceptual framework specifying the three dimensions of accessibility, this survey will systematically compare the theoretical arguments and empirical evidence by discussing successively the impact of compulsory licensing on affordability, availability and quality of HIV/AIDS drugs in the South. Thus, it appears that the debate is unresolved regarding the utility of compulsory licensing in the promotion of public health while its use is indeed rare and complicated in developing countries.